Breast conservation after neoadjuvant therapy for tumors ≥5 cm: A prospective cohort study. (2015) - Libson, Shai; Koshenkov, Vadim; Rodgers, Steven; Hurley, Judith; Avisar, Eli
Abstract: Introduction: Neoadjuvant therapy (NT) can facilitate breast conservation (BC). Similar oncologic outcomes have been reported with BC and mastectomy for T1 and T2 lesions, but studies of BC results for tumors ≥5 cm are limited. Our experience with BC for tumors ≥5 cm is reported. Patients and methods: A retrospective analysis of a prospectively collected database of all breast cancer patients treated with NT at our institution between 2003 and 2010 was performed to identify patients treated with BC for tumors ≥5 cm. Demographics, stage, tumor histology, pathologic response, tumor margins, failure patterns and rates, as well as survival rates were recorded. Results: Thirty patients treated with BC after NT for large tumors were identified. The only selection criteria for BC were technical ability with acceptable cosmetic results and negative margins. Patients with genetic predisposition for additional breast cancer were excluded. The mean follow-up was 43 months and the mean age at diagnosis was 51. The mean tumor size at diagnosis was 6.4 cm and the mean pathological size was 2.1 cm. Four of thirty (13.3%) had either systemic progression or regional recurrence. Three patients had systemic progression, 2 had regional recurrence and none had local recurrence. At a mean follow-up of 43 months, the success rate of BC on intent to treat basis was 96.7%, with an overall survival of 86.7% and disease-free survival of 83.3%. Conclusion: BC after NT is a safe option for carefully selected patients with tumors ≥5 cm. In this series, the oncologic results for the duration of the study were comparable to those reported after mastectomy.